Effects of Sex, Age, and Apolipoprotein E Genotype on Brain Ceramides and Sphingosine-1-Phosphate in Alzheimer’s Disease and Control Mice - den Hoedt, Sandra; Crivelli, Simone M.; Leijten, Frank P. J.; Losen, Mario; Stevens, Jo A. A.; Mané-Damas, Marina; de Vries, Helga E.; Walter, Jochen; Mirzaian, Mina; Sijbrands, Eric J. G.; Aerts, Johannes M. F. G.; Verhoeven, Adrie J. M.; et al. (Frontiers in Aging Neuroscience, 2021)
Apolipoprotein ɛ4 (APOE)4 is a strong risk factor for the development of Alzheimer’s disease (AD) and aberrant sphingolipid levels have been implicated in AD. We tested the hypothesis that the APOE4 genotype affects brain sphingolipid levels in AD. Seven ceramides and sphingosine-1-phosphate (S1P) were quantified by LC-MSMS in hippocampus, cortex, cerebellum, and plasma of <3 months and >5 months old human APOE3 and APOE4-targeted replacement mice with or without the familial AD (FAD) background of both sexes (145 animals). APOE4 mice had higher Cer(d18:1/24:0) levels in the cortex (1.7 fold, p=0.002) than APOE3 mice. Mice with AD background showed higher levels of Cer(d18:1/24:1) in the cortex than mice without (1.4 fold, p=0.003). S1P levels were higher in all three brain regions of older mice than of young mice (1.7 1.8 fold, all p≤0.001). In female mice, S1P levels in hippocampus (r = -0.54 [-0.70, -0.35], p<0.001) and in cortex correlated with those in plasma (r = -0.53 [ 0.71, -0.32], p<0.001). Ceramide levels were lower in the hippocampus (3.7–10.7 fold, all p<0.001), but higher in the cortex (2.3–12.8 fold, p<0.001) of female than male mice. In cerebellum and plasma, sex effects on individual ceramides depended on acyl chain length (9.5 fold lower to 11.5 fold higher, p≤0.001). In conclusion, sex is a stronger determinant of brain ceramide levels in mice than APOE genotype, AD background, or age. Whether these differences impact AD neuropathology in men and women remains to be investigated.